Doctrine, dynamic and difference : to the heart of the Lutheran-Roman Catholic 'differentiated consensus' on justification /: to the heart of the Lutheran-Roman Catholic 'differentiated consensus' on justification. (2012) - Witte, Pieter de
No abstract available